Answer:
[tex](-1;1)[/tex] and [tex](0;4)[/tex]
Step-by-step explanation:
First of all, even if the system is of 4th degree, by looking at the shape of the equations I am expecting up to 2 solutions.
The easiest way to solve it, since both equation are in the form y= something, is to equate both RHSs.
[tex]3x^2+6x+4=-3x^2+4\\6x^2+6x=0 \rightarrow 6x(x+1)=0[/tex]
which tells us that either [tex]x=0[/tex] or [tex]x=-1[/tex]
Now we can replace these value of x in one of the two to finish our work: [tex]x=0\rightarrow y= 4[/tex]
[tex]x=-1 \rightarrow y= -3+4=1[/tex]